Intention and sham: Heinrichs & Ors v Pantrust International SA & Ors [2018] JRC081A. Issue 10 (9th November 2018) - Alexander, Stephen
Abstract: An essential requirement for the creation of an express trust is the intention of the owner of the property to transfer that property to a trustee. Where such intention does not exist, but there has been an attempt to mislead or deceive third parties that it does, this may amount to a sham in certain circumstances. Where a sham exists, the trust will be invalid. The recent decision of the Jersey Court in Heinrichs & Ors v Pantrust International SA & Ors [2018] JRC081A provides important guidance on the identification and scope of sham.